Symptomatic Erythrocytosis Due to Homozygosity for Hb Luton [HBA2: c.269A>T (or HBA1)] and α-Thalassemia: A Clinical Update. (3rd March 2016) - Oliveira, Amelia; Warcel, Dana; Huntley, Nancy; Eleftheriou, Perla; Porter, John B.
Abstract: A female proband homozygous for both Hb Luton [α89(FG1)His→Leu (C A C>C T C), HBA2 : c.269A>T (or HBA1 )], a high oxygen affinity hemoglobin (Hb), and for α + -thalassemia (α-thal), (–α 4.2, leftward deletion) was first described in 2012. This is a follow-up report of the same case. At the age of 18, the described patient presented with progressively worsening lethargy, headaches, dizziness, syncope and Raynaud's phenomenon. Following extensive cardiological and neurological investigation, it was felt that significant erythrocytosis was the most likely cause. Venesection followed by regular exchange transfusions were arranged with marked amelioration in symptomatology. In the vast majority of cases of high oxygen affinity Hbs, venesection is not recommended due to the asymptomatic phenotype and reduced oxygen delivery resulting from venesection. This update describes the evolving phenotype of this unique proband and, to the best of our knowledge, the first use of regular, long-term therapeutic red cell exchange transfusions in a case of high affinity Hb.